الممارسات التسويقية في المؤسسات الاستشفائية الخاصة بين الواقع والمأمول - نجاة, بن فريحة; أنساعد, رضوان (Université de M'sila, 2020)
إن المؤسسات الصحية تلعب دور العامل المشترك في أي مجتمع من المجتمعات، ومع تنامي التطور الحضاري والاجتماعي والصناعي والإقتصادي، مؤديا بذلك إلى تزايد المشكلات الصحية وتزايد الطلب على الخدمات الصحية، مما جعل تلك المؤسسات تأخذ شكل مؤسسات أعمال متوسطة وكبيرة الحجم تهدف من خلالها لتقديم خدمات العلاج والوقاية إلى المرضى ثم الإرتقاء بمستوى الأداء لأقصى حد ممكن هذا من جهة وتحقيق عامل الربح من جهة أخرى. ونظرا لأهمية موضوع الممارسات التسويقية في المؤسسات الاستشفائية وحاجة هذه المؤسسات لها، فقد هدفنا من خلال هذه الورقة البحثية إلى تقديم مدى واقعية اعتماد المؤسسات الصحية على الممارسات التسويقية في التعريف عن نفسها لدى أفراد المجتمع معتمدين في ذلك إلى دراسة ميدانية لاحدى المؤسسات الاستشفائية الخاصة بولاية الشلف، كما توصلنا إلى عدة نتائج من أهمها أن التسويق الصحي لم يبلغ رواجه في المؤسسات الصحية لولاية الشلف. Abstract: Health institutions play the role of the common factor in any society, and with the growth of civilized, social, industrial and economic development, leading to an increase in health problems and an increase in the demand for health services, which made these institutions take the form of medium and large-sized business enterprises through which they aim to provide treatment services Prevention to patients and then the performance level up to the maximum extent possible this is on the one hand and the achievement of the profit factor on the other. Given the importance of the subject of marketing practices in hospital institutions and the need of these institutions for them, our goal through this research paper was to present the extent of the reality of health institutions relying on marketing practices to introduce themselves to community members, relying in this to a field study of one of the hospital institutions for Chlef Wilaya, We also reached several results, the most important of which is that health marketing has not reached its popularity in the health of Chlef wilay
Keywords: التسويق الصحي ; المؤسسات الاستشفائية ; ولاية الشلف ; الممارسات التسويقية